Balance of the Inertial Force and Inertial Moment of Crank Group Mechanism - Liu Yansong; Cao Jujiang (Jixie chuandong)
The inertia force and the inertia moment of the crank group mechanism are analyzed based on its characteristics. The balancing conditions of the inertia force and the inertia moment of the crank group mechanism are given and a practical balancing method is obtained. The results show that the balancing of inertia moment of the crank group can be achieved by the connecting rod with the centroid coordinates limited,when the balancing of the inertia force is achieved by adjusting the mass- radius product of the balance quality. The conclusions may be helpful for reducing the foundation vibration in the design of the crank group mechanism.